KARAKTER MUTU STRAWBERRY (Fragaria virginiana) SELAMA PENYIMPANAN DENGAN PERLAKUAN EDIBLE COATING CAMPURAN SORBITOL DAN PATI SAGU - Rafael Remit Winardi; Mintaria Harefa (Universitas Quality, 2018)
This study aims to determine the effect of the use of sorbitol and sago starch as edible coating on the quality of strawberry (Fragaria virginiana) during storage and to determine the quality and freshness quality of strawberries after the addition of sorbitol on the patisagu as edible coating during storage. ) Non factorial arranged factorial with 2 factors. Factor I: Comparison of sorbitol, sago starch and distilled water2 = concentration of 0 ml sorbitol (control) + 10 gram sago starch + aqudes 500 ml, S1 = concentorasisitbitol 1 ml + 10 gram sago starch + aqudes 500 ml, S2 = concentration of 3 ml sorbitol + 10 gram sago starch + aqudes 500 ml, S3 = 5 ml sorbitol concentration + 10 gram sago starch + aqudes 500 ml, S4 = 7 ml sorbitol concentration + 10 gram sago starch + 500 ml aqudes starch. Factor II is the length of storage, as long as 5 days. The results showed that the concentration of sorbitol and sago starch as edible coating on strawberry (Fragaria virginiana) quality during storage was not significantly different from weight loss with 1 ml sorbitol concentration at storage (2 days), ie 0.03%. It was also not significantly different from Vitamin C with the concentration of sorbitol 3 ml at storage (5 days), that is, 0.05%. Similarly, the total acid level was not significant with a concentration of 3 ml at storage (4 days), that is, 0.10%. And also the color followed was not significant with the concentration of 5 ml sorbitol at storage (4 days) which was 3.2%.